Experimental study and thermodynamic assessment of thermodynamic properties of pure Li2CO3 and K2CO3. (September 2022) - Qi, Jia; Yazhenskikh, Elena; Ziegner, Mirko; Wu, Guixuan; Müller, Michael; Sergeev, Dmitry
Abstract: In this work, the thermodynamic properties (heat capacity, transition temperature) and structure of Li2 CO3 and K2 CO3 were investigated experimentally using Differential Thermal Analysis (DTA), different types of Differential Scanning Calorimetry (DSC) and high temperature X-ray diffraction (HTXRD). The controversial solid-solid phase transition of Li2 CO3 was proved to be caused by impurities. The accuracy of the heat capacity for both carbonates was improved. The Gibbs energy data of these carbonates were reassessed in the new database, which can improve the accuracy in calculating and predicting the phase equilibria and thermodynamic properties in the corresponding multiple salt systems.